Environmental determinants of anaemia and its spatial association with Mosquito-Borne disease vulnerability: a case of Eastern and North-Eastern India - Lobsang Tshering Bhutia; Aparajita Chattopadhyay (Discover Public Health, 2025)
Abstract Background Understanding anaemia prevalence in the context of environmental exposure calls for in-depth research. This study delves into the clustering and determinants of anaemia, focusing on environmental factors and their association with mosquito-borne disease vulnerability in Eastern and North-Eastern India. Methods Using the National Family Health Survey (NFHS-5, 2019–21), Bivariate and Binary logistic regression analyses were used to determine the effect of environmental, health and demographic factors on anaemia separately for females and males, followed by spatial clustering of anaemia and its association with mosquito-borne disease vulnerability. Results The study reveals that anaemia was more likely to occur in females and males living in areas characterised by lower altitudes, higher mean annual temperatures, higher annual rainfall, more frequent drought episodes, and denser vegetation. Factors such as more number of children, being underweight, age 15–24, lower levels of education, being hHindu, tribal status, and belonging to the poorest wealth categories were also risk factors for anaemia. Furthermore, riverine areas of humid subtropical regions had a higher clustering of anaemia hotspots among females and males and were positively associated with areas of high mosquito-borne disease vulnerability in the study region. Conclusion The study underscores the significant role of environmental determinants in shaping anaemia risk in Eastern and North-Eastern India, calling for integrated, environment-informed public health interventions.